Corn Cost-Return Budget in North Central Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Dhuyvetter, Kevin C. (My University, 2014)
This publication provides estimated cost and returns for forward farm planning for corn production in north central Kansas.
MF2161_2014_02
Keywords: MF2161; Crops; Economics; MF